Kikuchi-Fujimoto Disease With Encephalopathy in Children: Case Reports and Literature Review - Pan, Yu-Ting; Cao, Li-Ming; Xu, Yan; Fan, Zhi-Dan; Yu, Hai-Guo (Frontiers in Pediatrics, 2021)
Context: Kikuchi-Fujimoto disease (KFD) is a benign and self-limiting disease characterized by regional lymphadenitis and low-grade fever. Encephalopathy may present in children with KFD. We present three cases of KFD with encephalopathy in children and a literature review. Evidence Acquisition: Literature published between 2010 and 2020 was reviewed to understand the clinical features, laboratory findings, and treatments for encephalopathy occurring in children with KFD. Results: The interval between KFD and onset of neurological symptoms was 10 days to 3 months. Laboratory results were normal, except for high protein levels in cerebrospinal fluid findings. Brain magnetic resonance imaging (MRI) findings include hyperintense T2 and FLAIR signal in the supratentorial white matter, deep gray matter, brain stem, cerebellum, temporal lobes, pons, and basal ganglia. Glucocorticoids and immunoglobulin could be effective for treating KFD with encephalopathy. Conclusions: The early clinical manifestations of KFD with encephalopathy in children lack specificity, and the diagnosis is mainly based on CSF analysis and brain MRI findings. Early and timely immunomodulatory therapy is effective and can improve the prognosis of patients with KFD with encephalopathy.